Fig tree xylophagous pest’s effects in the Bejaia region (central-north Algeria) - Chelli, Abdelmadjid; Oudjiane, Aldjia; Zebsa, Rabah; Razi, Sabah; Boussad, Fariza; Boudalia, Sofiane (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
In response to alerts from farmers in Bejaia region (central-north Algeria) about the decline of their fig trees, a survey was conducted between 2019 and 2021 in the main localities known for fig crops. Hypocryphalus scabricollis (Eichhoff) (Coleoptera, Curculionidae:  Scolytinae) was identified as the causal agent of fig tree decline in the region. This species is reported for the first time in Algeria. Here, a morphological description and main biological traits of this species are given. Distribution of H. scabricollis in the Bejaia region is illustred, and an overview of its behaviour, symptoms and damage caused to the host plant, and their potential impact in commercial fig production is discussed. This work aims to provide a preliminary database to the scientific community about this xylophagous pest of fig trees and to alert regional and national policy makers to take it seriously and address emerging bark beetle problems before it is too late.